ChemInform Abstract: The Different Roles of a Cationic Gold(I) Complex in Catalysing Hydroarylation of Alkynes and Alkenes with a Heterocycle. Issue 40 (September 2016) - Mehrabi, Tahmineh; Ariafard, Alireza
Abstract: Using DFT calculations, the mechanism of twofold hydroarylation of terminal alkynes with pyrrole catalyzed by a cationic gold(I) complex is investigated.